Development of Rempah Kita illustrated book to introduce spice diversity to children aged 7–12 - Cahyani, Wiwit; Setiaji, Rony Siswo (Universitas Negeri Yogyakarta, 2024)
This study aims to describe the process of development and material feasibility as well as the feasibility of the picture book media